2011
DOI: 10.1143/jpsj.80.094711
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Quantum Critical Endpoint in UCoAl

Abstract: Resistivity and magnetostriction measurements were performed at high magnetic fields and under pressure on UCoAl. At ambient pressure, the 1st order metamagnetic transition at H_m ~ 0.7 T from the paramagnetic ground state to the field-induced ferromagnetic state changes to a crossover at finite temperature T_0 ~11 K. With increasing pressure, H_m linearly increases, while T_0 decreases and is suppressed at the quantum critical endpoint (QCEP, P_QCEP ~ 1.5 GPa, H_m ~ 7 T). At higher pressure, the value of H_m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
111
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 61 publications
14
111
2
Order By: Relevance
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar experimental studies have revealed other wing-structure phase diagrams in UGe 2 [8,30,31] (also shown in Fig. 6 for comparison), Sr 3 Ru 2 O 7 [37], ZrZn 2 [9], UCoAl [35,36,40]. The behavior near the tricritical point could not be studied in Sr 3 Ru 2 O 7 and UCoAl because those compounds are already in the paramagnetic regime at ambient pressure.…”
Section: Quantum Wingsupporting
confidence: 61%
“…Besides UGe 2 and LaCrGe 3 , two ferromagnetic states have also been reported in ZrZn 2 [34]. In UCoAl, the anomaly corresponding to the field induced transition to the FM state shows two peaks in the ac susceptibility [35] and two kinks forming a plateau in electrical resistivity [36]. Two peaks in the ac susceptibility have also been reported in the metamagnetic transition of Sr 3 Ru 2 O 7 [37].…”
Section: Quantum Wingmentioning
confidence: 89%
“…7 is in excellent agreement with previous transport measurements. 10 Magnetization measurements 9 led to lower pressure dependence of B m , as mentioned above. This discrepancy probably comes from pressure inhomogeneities or differences in the crystal quality.…”
Section: Hall Effect Under High Pressurementioning
confidence: 69%
“…The metamagnetic transition at B m is of first order, attested by a hysteresis between increasing and decreasing field magnetization curves. 8,10 The hysteresis reduces and the metamagnetic transition gradually broadens as temperature increases, until it ends at T 0 = 12 K, marking the first-order critical end point (CEP). For T > T 0 a pseudo-metamagnetic transition fades out into a broad crossover region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation